Elections and its impact on democracy and business : a study of the Sarawak experience (with special reference to Bidayuh majority constituencies) - John, Nyigor. (Universiti Malaysia Sarawak (UNIMAS), 2002)
Participation of the citizenry in elections and thereafter collective involvement of the elected officials in the decision-making process are important ingredients for the gradual establishment of democracy. This paper seeks to identify the factors at play that has shaped the electoral process we now see in Sarawak and how these, in concert with others, have impacted democracy and the ensuing business that democracy sets out to serve.